A New Outlook on Mental Illnesses: Glial Involvement Beyond the Glue - Elsayed, Maha; Magistretti, Pierre J. (Frontiers in Cellular Neuroscience, 2015)
Mental illnesses have long been perceived as the exclusive consequence of abnormalities in neuronal functioning. Until recently, the role of glial cells in the pathophysiology of mental diseases has largely been overlooked. However recently, multiple lines of evidence suggest more diverse and significant functions of glia with behavior-altering effects. The newly ascribed roles of astrocytes, oligodendrocytes and microglia have led to their examination in brain pathology and mental illnesses. Indeed, abnormalities in glial function, structure and density have been observed in postmortem brain studies of subjects diagnosed with mental illnesses. In this review, we discuss the newly identified functions of glia and highlight the findings of glial abnormalities in psychiatric disorders. We discuss these preclinical and clinical findings implicating the involvement of glial cells in mental illnesses with the perspective that these cells may represent a new target for treatment.